2011
DOI: 10.1038/cdd.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

TLR-2 and TLR-9 are sensors of apoptosis in a mouse model of doxorubicin-induced acute inflammation

Abstract: Anthracycline antibiotics are inducers of an immunogenic form of apoptosis that has immunostimulatory properties because of the release of damage-associated molecular patterns. To study the mechanisms used by the innate immune system to sense this immunogenic form of cell death, we established an in vivo model of cell death induced by intraperitoneal injection of doxorubicin, a prototype of anthracyclines. The acute sterile inflammation in this model is characterized by rapid influx of neutrophils and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 39 publications
3
72
0
1
Order By: Relevance
“…Anti-inflammation treatments not only suppressed doxorubicin-caused myocardial inflammation but also prevented cardiaomyopathy (7)(8)(9). Previous studies suggested that the systemic inflammation was stimulated by tissue damage or cell apoptosis due to the toxicity of this drug (26). However, inflammatory responses triggered by tissue damage should be transient and self-restricted.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammation treatments not only suppressed doxorubicin-caused myocardial inflammation but also prevented cardiaomyopathy (7)(8)(9). Previous studies suggested that the systemic inflammation was stimulated by tissue damage or cell apoptosis due to the toxicity of this drug (26). However, inflammatory responses triggered by tissue damage should be transient and self-restricted.…”
Section: Discussionmentioning
confidence: 99%
“…2 Mechanistically, the immunogenic apoptotic bodies induced by exposure to doxorubicin are sensed by APCs through their TLR-2/TLR-9-MyD88 signaling pathways. 17 …”
Section: Apoptotic Cell Death As Icdmentioning
confidence: 99%
“…Recent evidence indicates that doxorubicin is able to induce immunogenic cell death (ICD) both in vitro (24) and in vivo (25,26), an effect mainly mediated by damage-associated molecular patterns (DAMP), including cell surface-exposed calreticulin (CRT), secreted ATP, and released high mobility group box 1 protein (HMGB1; ref. 27).…”
Section: Doxorubicin Enhances Lcl Immunogenicitymentioning
confidence: 99%
“…To verify whether the enhanced HMGB1 release showed by DX-LCLs could trigger receptordependent responses in an autocrine/paracrine fashion, we evaluated the expression of its functional receptor, TLR4, and of its downstream adaptor molecule Myeloid Differentiation primary response 88 (MyD88; ref. 26). Flow cytometry analysis showed that doxorubicin and cisplatin markedly increased the number of TLR4-expressing cells (63.3% and 54.4%, respectively) compared with control LCLs (38.1% of positive cells), whereas TPA Ăž NaB Ã 02 (top) and TLR4 (bottom) was analyzed by flow cytometry at t24, whereas CRT expression (center) was investigated after 3 hours.…”
Section: Doxorubicin Enhances Lcl Immunogenicitymentioning
confidence: 99%